Precipitation response to Heinrich Event-3 in the northern Indochina as revealed in a high-resolution speleothem record - Nguyen, Dung Chi (2023)
Heinrich Event-3 (HE-3) differs from other Heinrich Events (HEs) in terms of the strength of its expression in climatic records from different global localities. Here, we present new high resolution δ18O records from a composite speleothem record spanning from 31.5 to 28.4 ka within the HE-3 time interval. The record is obtained from two stalagmites collected from the Thuong Thien cave (TT), northern Vietnam, which exhibit growth rates of 0.12 to 0.68 mm/yr. The TT record shows a pronounced positive excursion of δ18O values of stalagmite in the time interval from 30.8 ka and lasted about one thousand years. Specifically, the δ18O reached maximum between ∼30.3–30.2 ka and returned to low values at 29.5 ka. Both the onset and termination phases of the excursion show gradual changes in δ18O values that form a relatively symmetric ‘V’ shape. The excursion suggests that the Indian Summer Monsoon (ISM), which modulates the climate and hydrology in the region, has endured dramatic weakening in response to HE-3. The timing and duration of the monsoonal decline are consistent with a significant slowdown of the Atlantic Meridional Ocean Circulation (AMOC), which probably drove the southward migration of the intertropical convergence zone (ITCZ) and consequently a decrease in precipitation over the Asian monsoonal region including northern Vietnam. To test the proposed mechanism, we further performed modeling simulations via an atmosphere general circulation model with a coupled slab ocean. Simulated results confirm both the scale and mechanistic connections between cooling in the North Atlantic and changes in precipitation at the Thuong Thien cave locality.